Mediating Mechanisms of the Incredible Years Teacher Classroom Management Program - Tveit, Håvard Horndalen; Drugli, May Britt; Fossum, Sturla; Handegård, Bjørn Helge; Klöckner, Christian A.; Stenseng, Frode (Frontiers in Psychology, 2020)
This study examined whether, and the extent to which, the Incredible Years Teacher Classroom Management programme predicted positive development of children's emotional, behavioural, and social adjustment through changes in the child-teacher relationship. Using data from a longitudinal quasi-experimental intervention trial with a matched control condition, including 1085 children (49,7% girls, Mage = 4.22 years; SDage = 0.88), the potential associations were tested by means of multilevel path modeling. The mediation model demonstrated that: 1) children in the intervention condition achieved more favourable changes in the child-teacher relationship than the control condition, 2) changes in the child-teacher relationship were associated with changes in the target outcomes, and 3) the intervention effects were mediated via changes in the child-teacher relationship.